A Review on Cutting-Edge Technology for Revitalizing and Reducing Water Pollution - Krishnakumar B. Vaghela; Devangee P. Shukla; Nayan K. Jain (Research Advances in Environment, Geography and Earth Science Vol. 4, 2024)
Because pollution control and improved treatment technologies are critical to tackling environmental sustainability challenges, adhering to environmental management standards is necessary for living a more sustainable lifestyle. Notably, rural inhabitants in both rich and low-income countries are becoming increasingly concerned about the quality of their water. Even while artificial intelligence (AI) can help with the majority of environmental sustainability issues, including water management, machine learning models can maximize water resource conservation. There is a large knowledge gap regarding the application of AI to water pollution mitigation. Long-term performance under ideal conditions for water resource conservation is decided by the ability to implement adaptive and sustainable water management techniques and technologies that ensure the successful use and conservation of water resources in the foreseeable future. Furthermore, the amount of pollution-related research—particularly advanced pollution control—published in the literature has expanded dramatically over the years and continues to do so. This review focuses on six key components of advanced water pollution management technologies: adsorption, ion exchanges, electrokinetic processes, chemical precipitation, phytobial remediation, and membrane technology. It also discusses how artificial intelligence can be used to regulate water pollution to protect environmental health, sustainability, and security. Water source protection involves the protection of surface water sources (e.g. lakes, rivers, man-made reservoirs) and groundwater sources (e.g. spring protection, dug well protection, and drilled well protection) to avoid water pollution (see also pathogens and contaminants). Water quality is more difficult to maintain due to data gaps and pollution’s impact on dimi water quality. As a result, a complete system or strategy for water security and pollution management is required to handle water-related challenges and give a thorough approach to water problem solving.